(untitled) (Revista de Estudos da Linguagem, 2024)
This article addresses the alternation between plural forms of names whose singular ends in a falling oral diphthong finishing with -u, as in pneus pneis (tires), espanhóis espanhous (Spanish). The aim is to contribute to the understanding of this alternation in Brazilian Portuguese and to address the issues related to the variation, processing and representation of complex words in the lexicon as well. Data were obtained through an elicited production test with pseudowords and random collection of spontaneous production (Labov, 1972; Sankoff, 2004). The analysis was conducted based on the assumptions of exemplar-Models (BYBEE, 2010), according to which representations of wordforms in the lexicon are both detailed and abstract (Pierrehumbert, 2012) and are organized in networks based on sound and semantic similarity. Furthermore, morphological patterns emerge from the representations in the lexicon, which are affected by words’ token frequency and by the type frequency of the emerging patterns. The experimental results showed that the effect of linguistic constraints such as the size of the stimuli, according to the number of syllables, and that of the nucleus of the diphthong, is related to the type inferred by the participant, which is highly correlated to its level of schooling. The comparison with results from other studies reinforces the effect of the speaker’s sociolinguistic experience together with the actuation of innate cognitive mechanisms. The spontaneous speech data confirms the competition of the two plural patterns over the word’s representations in the lexicon as observed in the experimental data.